The letter Q : queer writers' notes to their younger selves - Moon, Sarah, 1982-; Lecesne, James (Arthur A. Levine Books, 2012)
Collects letters from such famous contributors as Brian Selznick, Michael Cunningham, and Amy Bloom to offer hope and support in the face of prejudice.